Importance of optimization of functionalization of single walled carbon nanotube with special reference to mechanical, viscoelastic and adhesive characteristics of vinyl terminated polydimethyl siloxane. (3rd January 2019) - Roy, Rinu Elizabeth; Vijayalakshmi, K.P.; Rajeev, R.S.
Abstract: This paper highlights the structure-property relationship of optimally functionalized single walled carbon nanotube (SWCNT) incorporated vinyl terminated polydimethyl siloxane (VPDMS). Our previous studies revealed that functionalization of SWCNTs for 4 h (FSWCNT-4) incorporates maximum concentration of functional groups with least defects on the nanotube surface. Hence, to validate the utility of FSWCNT-4 in VPDMS, nanocomposites with different concentration of nanotubes were prepared through platinum catalysed hydrosilylation route where the processing conditions were controlled through ultrasonication. When the physico-mechanical properties of these nanocomposites were compared with those prepared using nanotubes functionalized for different extent of time, it was found that a better interaction between VPDMS and SWCNT observed for the composite containing nanotubes functionalized for 4 h (FSWCNT-4). The polymer-filler interaction in these nanocomposites was reflected in the improved mechanical and thermal properties which were attributed to the optimum extent of functionalization of the nanotube. The site of interaction between VPDMS matrix and the functionalized nanotubes has been identified through computational studies. Mechanical properties proved that the interaction of cyclic siloxane groups of VPDMS with hydroxyl groups in nanotubes was the maximum for FSWCNT- 4 imparting an enhancement of 220% in tensile strength and 272% in modulus. Thermal stability, thermo-oxidative stability and adhesive characteristics of the polymer were improved when the composites were prepared using optimally functionalized single walled carbon nanotube. Graphical abstract: Highlights: Literature on VPDMS-optimally functionalized SWCNT are scarce. Nanotube functionalization optimized for better interaction with VPDMS. Optimally functionalized carbon nanotubes impart superior properties to VPDMS. Adhesive and mechanical improved with optimally modified nanotube addition. Interaction sites between VPMDS and CNT established via computational studies.